1976
DOI: 10.1139/f76-009
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Rainbow Trout (Salmo gairdneri) to Electroshock

Abstract: Electroshocking elicited an immediate increase in plasma corticoid and lactate concentrations and thrombocyte:leucocyte ratio in rainbow trout (Salmo gairdneri). Plasma glucose concentrations increased significantly after 3 h. Plasma protein, calcium, magnesium, and androgen levels were not measurably affected. Plasma lactate returned to preshock levels within 3 h, but corticoid and glucose concentrations remained elevated for at least 6 h. The fish coughed violently or did not resume normal breathing rates fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 16 publications
6
51
1
Order By: Relevance
“…However, the feral catfish, demonstrated significantly higher PCV, Hb, MCV, MCH, lymphocytes, monocytes and eosinophils values (p=0.001 for all except monocytes with p=0.01). Higher hematological parameters might have resulted from the difference in water temperature and oxygen concentration of the culture environment (Kocabatmaz & Ekingen, 1978); while an increase in leucocytes has been attributed to stress conditions; which is more common under feral condition relative to the more conducive pond environment (Schreck et al 1976). High MCV suggests that a hemo-dilution mechanism is operational; the mean corpuscular volume gives an indication of the status or size of the red blood cells and reflects an abnormal/ normal cell division during erythropoiesis.…”
Section: Resultsmentioning
confidence: 99%
“…However, the feral catfish, demonstrated significantly higher PCV, Hb, MCV, MCH, lymphocytes, monocytes and eosinophils values (p=0.001 for all except monocytes with p=0.01). Higher hematological parameters might have resulted from the difference in water temperature and oxygen concentration of the culture environment (Kocabatmaz & Ekingen, 1978); while an increase in leucocytes has been attributed to stress conditions; which is more common under feral condition relative to the more conducive pond environment (Schreck et al 1976). High MCV suggests that a hemo-dilution mechanism is operational; the mean corpuscular volume gives an indication of the status or size of the red blood cells and reflects an abnormal/ normal cell division during erythropoiesis.…”
Section: Resultsmentioning
confidence: 99%
“…This corresponds with a previous study by Roth et al (2007b) where use of computer imaging on post rigor filleted and unbled turbot revealed that percussive killed fish had higher reddishness and less whiteness than and electrically stimulated carcasses. Forcing blood out using electrical stimulation might only be feasible in newly killed animals, as electrical exposure on a live specimen would cause an autonomic release of catecholamines (Schreck et al 1976), potentially known to redirect the blood from the gut and into muscles (Farrell et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Schreck et al (1976) reported similar findings for electroshocked rainbow trout. In contrast, Barton and Grosh (1996) found that granulocytes (neutrophils and thrombocytes) declined within the first 15 min after shocking.…”
Section: Discussionsupporting
confidence: 66%
“…There is also evidence that a brief electroshock influences specific immune function of fish by altering the abundance of circulating leucocytes. Schreck et al (1976) found that rainbow trout exposed to a brief electroshock (230 volts; 2.3 amperes) exhibited an immediate but transient increase in the number of circulating thrombocytes, while granulocytes (e.g. neutrophils) may decline in response to an electroshock (Barton and Grosh 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation